Level of Knowledge of Hypertension Patients and Compliance with Treatment at Sirnajaya Health Center - Ramadhani, Alya; Nasution, Lailan Safina (Muhammadiyah Medical Journal, 2023)
Background: Uncontrolled hypertension is the most common and important risk factor for cardiovascular diseases, which can lead to complications or even death. Uncontrolled hypertension can be caused by noncompliance with hypertension medication instructions. One factor contributing to the disobedience of hypertension medication instructions is the level of knowledge on hypertension. Purposes: This study analyzed the correlation between patients’ hypertension knowledge and hypertension medication compliance in Sirnajaya Health Center, Bekasi, West Java, Indonesia. Methods: A cross-sectional study was conducted among 62 hypertension patients in Sirnajaya Health Center in December 2022. They were asked to answer the Hypertension Knowledge-Level Scale (HK-LS) questionnaire and the Morisky Medication Adherence Scale-8 (MMAS-8) to assess their hypertension knowledge and compliance with the hypertension medication. The chi-squared test was used to determine the correlations between the variables. Results: There were 36 respondents (58.1%) with low knowledge and 39 respondents (62.9%) with low medication compliance. Analysis through the chi-squared test reveals a correlation between knowledge level and medication compliance (p 0.001). Conclusion: There was a correlation between hypertension knowledge and compliance in consuming hypertension medication among the hypertension patients of Sirnajaya Health Center, Bekasi, West Java, Indonesia.